Budget Allocation System of a Highly Urbanized Local Government Unit in Central Luzon, Philippines - Lorenzo, Evangeline; Paguio, Darwin; R. Asio, John Mark (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2021)
The study determined the local planning and budget process of a highly urbanized local government unit (LGU) in Central Luzon, Philippines. It involves all department concerns and civil society organizations (CSOs) that use the City's local governance performance management system (LGPMS). The researchers used a descriptive research study to obtain the necessary data from a survey to seventy-five (75) rank and file employees. The researchers used a purposive sampling technique to gather the respondents involved in planning, budgeting, and managing programs and projects. With a self-made instrument that underwent validity, the researchers gathered the essential data for the study. The data were statistically analyzed using frequency, percentage distribution, analysis of variance (ANOVA), and t-test for independent variables. Preliminary results illustrated that respondents' status was in regular status as division head level, and their years of service were more than sixteen (16) years. The statistical analyses revealed no significant variations in the assessment on the budget allocation system of the local government unit (LGU) as determined on its indicators. The management also agrees that employees work effectively in the budget allocation of the local government unit. The study recommended the orientation and assessment on the current allocation and budget process wherein the department's prioritization can review the objectives and policy decisions.